2022
DOI: 10.1155/2022/2260083
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Silver Trimolybdate (Ag2Mo3O10.2H2O) Nanorods: Synthesis, Characterization, and Photo‐Induced Antibacterial Activity under Visible‐Light Irradiation

Abstract: The present study reports the synthesis, characterization, and antibacterial properties of silver trimolybdate (Ag2Mo3O10.2H2O) nanorods. The synthesis was performed using a conventional hydrothermal method. The sample was characterised by scanning electron microscopy (SEM), X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, UV–Vis–NIR diffuse reflectance, thermogravimetric analysis (TGA), and differential scanning calorimeter (DSC). The direct antibacterial activity was evaluated using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%